المسؤولية المدنية للمدير في شركة المساهمة المفلسة - الأسود, صابر; مقى, نورالدين (My University, 2023)
المسؤولية المدنية للمدير في شركة المساهمة المفلسة من المواضيع المهمة في مجال قانون الأعمال، وذلك مرده للدور المهم للشركات المساهمة التي تعتبر قوام الاقتصاد الوطني والدافع بعجلة الاستثمار، لذا شدد المشرع التجاري من هاته المسؤولية، واشترط لقيامها مجموعة من الشروط؛ بدءا بتوفر الشروط القانونية للعضوية في مجلس الإدارة، ثم وقوع الشركة في الإفلاس مع عجزها عن تسديد ديونها بصدور حكم قضائي نهائي. فإذا ثبت مسؤولية المدير عن إفلاس الشركة المساهمة يمد الحكم بالإفلاس إليهم، فهم مسؤولون شخصيا عن إفلاس الشركة، إضافة إلى ذلك يمكن الزامهم بدفع ديون الشركة المفلسة كالشريك المتضامن في شركة التضامن، وذلك حتى يقع الاطمئنان في نفوس المتعاملين مع الشركة، وحماية لهذا النوع من الشركات من تبديد أمواله.The responsibility of the Board of Directors for the bankruptcy of the joint stock company is one of the important topics in the field of business law, given the important role of joint stock companies, which are the strength of the national economy and the motivation for investment, the commercial legislator stressed this responsibility, and stipulated for its establishment a set of conditions; starting with the availability of legal conditions for membership in the Board of Directors, and then the company's fall into bankruptcy with its inability to pay its debts with the issuance of a final judicial ruling. If the Board of Directors is found responsible for the bankruptcy of the joint stock company, the bankruptcy judgment is extended to them, they are personally responsible for the bankruptcy of the company, in addition to that they can be obliged to pay the debts of the bankrupt company as a joint venture partner in the solidarity company, so that the company's customers can be reassured and protect this type of company from squandering its funds.
مذكرة ماستر
Keywords: المسؤولية المدنية- الشركةالمفلسة - الاقتصاد الوطني- الاستثمار التجاري: civil liability - bankrupt company - national economy - commercial investment